1911
DOI: 10.1002/cber.191104403216
|View full text |Cite
|
Sign up to set email alerts
|

Über Cyclo‐octatetraen

Abstract: Unscre crsten Anwendungen der Hydrierungcn init Hilfe von Platin geschahen bci liochrnolekularen Alkoholen (Phytol, Cholcsterin, Oleinnlkohol, Emcylalkoliol), Kohlenwasserbtoffen (Phyten, Cjcloocten), einern Terpenalkohol (Geraniol), Alkaloiden und anderen ungesiittigten Basen (Tropidin, Dimethylpiperidin, Dimethylgranatsnin), Peroxyden (zur Bestimmong ihrer Struktur), endlich betrafen sie die Reduktion des arornatisclien Kernes (Benzoesiure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 14 publications
0
92
0
6
Order By: Relevance
“…176 The C60 n-(n > 0) was taken as a model for the cage of endohedral metallofullerenes. It was found that the reaction becomes more exothermic (and the barrier is reduced) for the [5,6] attack when n increases from 0 to 6 electrons (see Fig. 5).…”
Section: Aromaticity Determines the Regioselectivity Of Diels-alder Rmentioning
confidence: 92%
See 4 more Smart Citations
“…176 The C60 n-(n > 0) was taken as a model for the cage of endohedral metallofullerenes. It was found that the reaction becomes more exothermic (and the barrier is reduced) for the [5,6] attack when n increases from 0 to 6 electrons (see Fig. 5).…”
Section: Aromaticity Determines the Regioselectivity Of Diels-alder Rmentioning
confidence: 92%
“…5). On the other hand, for the [6,6] addition the exothermicity is somewhat reduced (and the barrier increases) when n increases. For n = 4-5, there is a change in the regioselectivity of the process and the [5,6] becomes the preferred attack.…”
Section: Aromaticity Determines the Regioselectivity Of Diels-alder Rmentioning
confidence: 97%
See 3 more Smart Citations